BETWEEN FACTS AND NARRATIVES: THE CRIME IN SKELA 1941 IN LOCAL AND NATIONAL MEMORY CULTURE - Tucović, Radosav; Stipić, Davor (National interest, 2026)
The crime in the village of Skela was committed on August 15, 1941 by members of the 64th Reserve Police Battalion. It was an act of reprisal, but at the same time also an act of revenge for the deaths of one officer and three non-commissioned officers of the same battalion, who had been killed in the village the previous day. The reprisal was ordered by the Military Commander of Serbia, General Dankelmann, together with his closest associates, and it was decided that news of the crime should be publicly announced through all available channels of communication. The aim was to intimidate the local population across the entire occupied territory and thereby deter further attacks on German soldiers and police personnel.Unlike other crimes committed in the autumn of 1941, this crime did not acquire a central place in the national culture of memory, but remained confined exclusively to the local context. The main facts concerning the crime were established during two trials held in 1947; nevertheless, over time a wide range of inaccuracies, and even serious errors emerged in collective memory. In historiography, the basic factual framework of the crime was established more than half a century later, in the late 1990s.By contrast, the culture of memory assumed various forms, with differing degrees of accuracy. Numerous articles addressing this crime were published in the press; however, they often contained a series of erroneous data, which clearly contributed to the creation of a distorted narrative based on incorrect assumptions. In the village itself, two significant monuments were erected, directly marking and preserving from oblivion both the site of the reprisal and the names and faces of the murdered villagers. In addition, streets in the village were named after the victims, while the main village street was dedicated to all those who perished in the massacre. Finally, oral tradition remains alive to this day, focusing primarily on the general narrative of the burning of the village and the execution of hostages, as well as on individual stories of the victims, preserved from oblivion by their descendants.
Keywords: World war Two; Occupied Serbia; Socialist Yugoslavia; Culture of Memory; Crimes; Skela